Millets and pseudo cereals : genetic resources and breeding advancement - Singh, Mohar; Sood, Salej (Woodhead Publishing, 2021)
Millets and Pseudo Cereals is the first comprehensive resource to focus on the potential crop improvements through genetic enhancements. ... Millets and Pseudo Cereals presents current information on the genetic architecture of important economic traits and the genomic resources for gene enabled breeding. This compilation contains information on the global status, available germplasm resources, nutritional value, breeding advancements, genomics applications and sustainability of agriculture through millets and pseudo-cereals cultivation. This book is a valuable resource for those conducting research and exploring new areas for advancing crop genetic understanding.. --